2013
DOI: 10.1103/physrevb.87.184116
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron diffraction study of relaxation and rumpling of ferroelectric domains in BaTiO3(001)

Abstract: The surface of a ferroelectric BaTiO 3 (001) single crystal was studied using synchrotron radiation induced x-ray photoelectron diffraction (XPD), x-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), and low-energy electron diffraction (LEED). AFM, XPS, and LEED show that the surface is BaO terminated with a (1×1) reconstruction. The Ba 4d, Ti 2p, and O 1s XPD results were compared with multiple scattering simulations for out-of-(P + ,P − ) and in-plane (P in ) polarizations using a genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…For Sr 3d we assumed Sr = 4.8 nm [47]. From a layer-by-layer attenuation model [48], we derive the fraction f of the total Sr 3d spectrum due to surface Sr atoms considering a (La, Sr)O-terminated surface f = 0.328, which, compared to the experimental value f = 0.311, suggests that the LSMO surface is mainly (La,Sr)O terminated. Although La 3d and Mn 2p core electrons have comparable escape depths of 1.6-1.9 nm [47], the La 3d cross section is more than three times that of Mn 2p; furthermore, if the MnO 2 is below the (Sr, La)O layer, then it will be more strongly attenuated.…”
Section: B X-ray Photoelectron Spectroscopymentioning
confidence: 95%
“…For Sr 3d we assumed Sr = 4.8 nm [47]. From a layer-by-layer attenuation model [48], we derive the fraction f of the total Sr 3d spectrum due to surface Sr atoms considering a (La, Sr)O-terminated surface f = 0.328, which, compared to the experimental value f = 0.311, suggests that the LSMO surface is mainly (La,Sr)O terminated. Although La 3d and Mn 2p core electrons have comparable escape depths of 1.6-1.9 nm [47], the La 3d cross section is more than three times that of Mn 2p; furthermore, if the MnO 2 is below the (Sr, La)O layer, then it will be more strongly attenuated.…”
Section: B X-ray Photoelectron Spectroscopymentioning
confidence: 95%
“…Höfer et al . showed that the signature of these surface charges can persist up to 510 K. Rumpling, reconstruction and relaxation, associated with the FE state, can be considerably altered at the surface 26 , 27 . However, although enhanced surface tetragonality due to the outward movement of oxygen ions may favor polarity 24 it does not necessarily explain the persistence of different polarization states.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies will potentially allow determining how general our findings are, when bearing in mind, e.g., that using other methods, the surface structure of BaTiO 3 thin films has been characterized sometimes as a monolayer of a Ti‐O phase and sometimes as a BaO structure . Obviously, other surface structures can be formed when the BaTiO 3 is interfacing other heteroepitaxial engineered layers rather than the vacuum (e.g., as in the case of engineered vortex structures that have garnered much interest recently).…”
Section: Resultsmentioning
confidence: 89%